Impact on core values of family medicine from a 2-year Master’s programme in Gezira, Sudan: observational study - Mohamed, Khalid Gaffer (BMC Fam Pract, 2019)
BACKGROUND: Training of family physicians should include not only clinical and procedural skills, but also core values as comprehensive care, continuity of care, leadership and patient-centeredness. The Gezira Family Medicine Project (GFMP) is a 2 years Master’s programme in family medicine in Sudan. We assessed the impact of GFMP on the candidates’ adherence to some core values of family medicine. METHODS: This is a prospective study with before-after design based on repeated surveys. We used Patient-Practitioner Orientation Scale (PPOS) to assess physicians’ attitude towards patient-centeredness. Practice based data from individual patients’ consultations and self-assessment methods were used to assess physicians’ adherence to core values. RESULTS: At the end of the programme the candidates (N = 110) were significantly more active in community health promotion (p <  0.001), more confident as a team leader (p = 0.008), and showed increased adherence to national guidelines for managing diabetes (p = 0.017) and hypertension (p = 0.003). The responding candidates had more knowledge about patients’ medical history (p <  0.001), family history (p < 0.001) and family situation (p < 0.001). There were more planned follow up consultations (p < 0.001) and more referrals (p = 0.040). In contrast, results from PPOS showed slightly less orientation towards patient-centeredness (p = 0.007). CONCLUSIONS: The GFMP Master’s programme induced a positive change in adherence to several core values of family medicine. The candidates became less patient-centered.